Working Capital Management and Profitability: An Analysis of Listed Commercial Banks in Sri Lanka - Gamlath, G.R.M.; Rathiranee, Y. (University of Jaffna, 2012)
Decisions relating to working capital and short term financing are referred to as working capital management. These involve managing the relationship between a firm's short-term assets and its short-term liabilities. The goal of working capital management is to ensure that the firm is able to continue its operations and that it has sufficient cash flow to satisfy both maturing short-term debt and upcoming operational expenses. Working capital management is one of the essential determinants of firms’ market value because it directly affects the profitability. This study investigates the relationship between working capital management and profitability of Colombo Stock Exchange (CSE) listed commercial banks in Sri Lanka. The objective of the study is to identify the linkage between the working capital management and profitability and its impact on profitability. The relation between the working capital management and profitability is examined using Pearson’s correlation analysis and the effects on profitability is found out using the regression analysis by using a sample of 07 annual financial statements of listed commercial banks in Sri Lankan covering period 2007- 2011. The working capital management consists of the variables of current ratio (CR), loan to deposit ratio (LDR) and cash ratio (CSR) and the profitability represents the net profit margin (NPM), return on assets (ROA) and return on capital employed (ROCE). According to Pearson’s correlation analysis, the dependent variables; NPM & ROA has a positive insignificant relationship with all independent variables where as the dependent variable ROCE has positive relationship with LDR & CSR and has a negative relationship with CR. According to the Regression analysis, the CSR has great impact on NPM and ROA than other components which are influenced by other factors such as savings, interest rates other than current ratio and Loan to Deposit ratio. Therefore, working capital management has a great impact on the profitability with keeping an optimal level of liquidity of the Sri Lankan listed commercial banks and the value of the managers of commercial banks will have to increase value of the firm thereby controlling the level of optimal working capital position.
Keywords: Working Capital Management; Profitability; Current ratio; Loan to Deposit ratio; Cash ratio